2015
DOI: 10.1002/anie.201505608
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Piperazines Enabled by Visible‐Light Irradiation and Aluminum Organometallics

Abstract: The development of more active C–H oxidation catalysts has inspired a rapid, scalable, and stereoselective assembly of multifunctional piperazines through a [3+3] coupling of azomethine ylides. A combination of visible-light irradiation and aluminum organometallics is essential to promote this transformation, which introduces visible-light photochemistry of main-group organometallics and sets the basis for new and promising catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…[35i] Modification of the tpa ligand to form ad inuclear,r igid complex has been found to retain the oxidative activity but to suppress significantly the nonproductive formation of m-oxo dimers ([Fe(L3) 2 ] 4 + ). [54] Beller [35b, c, 55] and Bolm [56] have shown that in situ formed iron complexes with simple amine/picolinic acid derivatives or amino alcohols as ligands are capable of stereoselective oxidations. More recently, an in situ assembled hexadentate iron complex has been demonstratedt o catalyzee fficientlym etal-based aliphatic CÀHo xidation ([Fe(L4) 2 ](OTf) 2 ).…”
Section: Novel Catalystdesignmentioning
confidence: 99%
“…[35i] Modification of the tpa ligand to form ad inuclear,r igid complex has been found to retain the oxidative activity but to suppress significantly the nonproductive formation of m-oxo dimers ([Fe(L3) 2 ] 4 + ). [54] Beller [35b, c, 55] and Bolm [56] have shown that in situ formed iron complexes with simple amine/picolinic acid derivatives or amino alcohols as ligands are capable of stereoselective oxidations. More recently, an in situ assembled hexadentate iron complex has been demonstratedt o catalyzee fficientlym etal-based aliphatic CÀHo xidation ([Fe(L4) 2 ](OTf) 2 ).…”
Section: Novel Catalystdesignmentioning
confidence: 99%
“…[1,2] Processes involving the allene moiety together with another hydrocarbon unsaturation have attractedc onsiderable attention recently. [1,2] Processes involving the allene moiety together with another hydrocarbon unsaturation have attractedc onsiderable attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…At present, organolithiums do not engage in this reaction. On the sulfoxide side, substrates bearing aferrocene (2j), [22] as well as thiomorpholine (2m)a nd thioflavanone heterocycles (2s,t), further expand the potential of this reaction to impact ligand [3,23] and drug design. [1b, 24] Remarkably, b-heteroatoms and even unprotected ketones are tolerated (2m,s,t), further suggesting the unusual organometallic species which enable this reaction (entries 4a nd 5; Scheme 2a).…”
mentioning
confidence: 99%